Assessment of Color Difference of Translucent Zirconia Substructure Veneered Using a Layering Technique with Two Different Veneering Thicknesses: An in-vitro study - Noora Berhaim; Nourelhouda Misurati; Milad Eshah; Mohamed Zeglam; Hager Ashiki (Khalij-Libya Journal of Dental and Medical Research, 2022)
Background and objectives. The introduction of zirconia to the dental field created a path for development of new designs and applications, but still, a minimum framework thickness of 0.5 mm with the remaining thickness of the restoration used for building the ceramic veneer was always recommended. This might have possibly affected the final shade of the restoration due to the whitish color of Y-TZP. This in vitro study was designed to assess the color difference of translucent zirconia substructure veneered using a traditional layering technique with two different veneering thicknesses. Methods. A total of twenty translucent Ice zirconia disc samples with standardized dimensions 12 mm in a diameter, 0.5mm in thickness were designed and constructed using zirkonzahn system. The samples were classified into two groups: Group I: (n = 10) veneered by 0.5 mm thickness layering technique using IPS emax Ceram dentin shade A2. Group II (n = 10) veneered by 1 mm thickness layering technique using IPS emax Ceram dentin shade A2. Twenty composite resin discs 12mm in diameter and 5mm in thickness in A3 shade, were fabricated to be bonded to ceramic specimens using Dual-curing translucent rely X Unicem automix Self-Adhesive Resin luting cement. Spectrophotometer was used to measure color parameters L*, a*, b* for all samples. ΔE values were measured to determine color differences between the specimens and the A2 VITA classical shade (target shade). ΔE values were compared with an acceptability threshold (ΔE=3.7). Independent t-test was used to analyze data (P<0.05) in this study and was analyzed using (SPSS) software, version 22. Results. The results showed that veneering thicknesses had a significant effect on the mean (ΔE) Values at P ≤ 0.001. The 0.5 mm veneer thickness showed the higher significant mean color difference (∆E) than the 1.0 mm veneering thickness where the recorded mean (ΔE) Values were (4.15±1.31) (2.65±1.39) respectively at p ≤ 0.001. Conclusions. This study concluded that 1.0 mm veneer thickness was the optimum thickness regarding color matching.